Antioxidant and preliminary phytochemical studies of anethum graveolens - AMRITA KUMARI SRIVASTAVA,; DEVESH KUMAR KUSHAWAHA,; GEETA WATAL, (International Journal of Pharma and Bio Sciences, 2017)
Plants being rich in polyphenols are an important source of natural antioxidants which can neutralize free radicals generated in the system responsible for causing oxidative stress during diabetes. The present study deals with phytochemical screening and in vitro assessment of antioxidant potential of aqueous leaves extract of Anethum graveolens. The phytochemical analysis of the extract revealed the presence of tannins, saponins, carbohydrates, glycosides, alkaloids, flavonoids and proteins. The total phenolics and flavonoids contents present in the A. graveolens leaves extract were 66.5 mg of Gallic Acid Equivalent (GAE)/g and 29.8 mg of Quercetin Equivalent (QE) /g respectively. Significant antioxidant efficacy of A. graveolens leaves was further confirmed by percent inhibition of DPPH., NO., O2- radicals, OH radicals, ABTS+ radicals and Metal Chelating efficacies as it was found to be 87.57, 68.29, 82.32, 74.02, 97.05 and 61.51% inhibition respectively. Therefore, the data suggest that the aqueous extract of A. graveolens leaves could be developed not only as an anti-aging agent but also as an agent for managing oxidative stress due to diabetic complications.